2019
DOI: 10.1001/jamainternmed.2018.7117
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning in Medicine—Promise, Progress, and Challenges

Abstract: Recent years have seen a surge of interest in machine learning and artificial intelligence techniques in health care. 1 Deep learning 2 represents the latest iteration in a progression of artificial intelligence technologies that have allowed machines to mimic human intelligence in increasingly sophisticated and independent ways. 3 Early medical artificial intelligence systems relied heavily on experts to train computers by encoding clinical knowledge as logic rules for specific clinical scenarios. More advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
174
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 320 publications
(208 citation statements)
references
References 10 publications
1
174
0
5
Order By: Relevance
“…For instance, Topol et al reported that out of the five studies using deep learning in pathology (with results compared to physicians), one study only was prospective in nature utilizing AHI in breast cancer metastases . Thus, there is a need to develop both data quality and quantity to potentiate the powers of ML tools . This study supports that the current quality of studies pertaining ML is suboptimal, and there is an imperative need to improve both quality and quantity of data before the prospective application of these models in medical practice.…”
Section: Discussionmentioning
confidence: 55%
“…For instance, Topol et al reported that out of the five studies using deep learning in pathology (with results compared to physicians), one study only was prospective in nature utilizing AHI in breast cancer metastases . Thus, there is a need to develop both data quality and quantity to potentiate the powers of ML tools . This study supports that the current quality of studies pertaining ML is suboptimal, and there is an imperative need to improve both quality and quantity of data before the prospective application of these models in medical practice.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, inter-professional teaching would greatly benefit from the rapid development of education technology. Initiatives such as blended teaching [15], serious games [16], virtual patients [17], virtual team play [18] and very soon, machine learning [19] will totally transform the education of health professionals. Such fundamental changes are urgently needed to attract more young and promising learners of both genders into the field of health.…”
mentioning
confidence: 99%
“…On the other hand, the increase in neuronal population activity also increases local blood flow leading to more glucose and oxygen entering a neuron (see review on neurovascular coupling: 21 ). This activity dependent energy supply can be expressed as: + 2 (∑ ) 2 , where xk represents spiking activity of neuron k from a local population of K neurons ( ∈ {1, … , , . .…”
Section: Synaptic Learning Rule Derivation By Maximizing Neuron Energmentioning
confidence: 99%
“…However, networks that use backpropagation have multiple properties which are difficult to reconcile with biological networks. For example: (1) they require separate phases for sending a bottom-up 'sensory' signal and for receiving a top-down error signal, whereas in the brain top-down feedback is combined with incoming sensory information; (2) backpropagation requires symmetric weights, meaning that a synaptic connection from neuron A to B has to have exactly the same strength as connection from B to A; (3) neuron models are biologically unrealistic as they do not include, for example: spiking activity, internal neuron dynamics, or Dale's law (either excitatory or inhibitory neurons), among many other simplifications. This question of how to bridge the gaps between biological and artificial learning algorithms is a subject of rapidly growing research at the intersection of neuroscience and computer science [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%